Programa de incentivos no económicos, para el personal de obra en sector de la construcción (2018)
The system of unpaid incentives for construction workers, is an investigation paper that focuses on the development of a program of mutual benefit, in which workers can reach a series of complementary benefits to their nominal income and the enrolment in the benefit programs of the national legislation; so that it will also give the employer an improvement in their productivity rate among their work group. The structure of the research is based on some of the most important motivational and human behavior theories that allow to break down the elementary principles of the worker's needs; also the study of administrative models that allow for effective application of the different incentive programs.